Heavy metal pollution and Pb isotopic tracing in the intertidal surface sediments of Quanzhou Bay, southeast coast of China. Issue 1 (15th April 2016) - Yu, Ruilian; Zhang, Weifang; Hu, Gongren; Lin, Chengqi; Yang, Qiuli
Abstract: Concentrations of 16 heavy metals and Pb isotopic ratios in the intertidal surface sediments of Quanzhou Bay were determined to study the pollution level of heavy metals and the sources of Pb. The results showed that most concentrations of Cd, Sn, Mn, Cu, Zn, Cr, Pb, Hg, Ni, Co, Cs, Fe and V were higher than the background values, while most concentrations of Ti, Sb and Sr were lower than the background values. The mean concentrations of Cu, Zn, Pb, Cr and Cd exceeded the first-grade criteria of Chinese marine sediment quality. The geo-accumulation indexes revealed that the sediments had been polluted by some heavy metals. The results of Pb isotopic tracing indicated that the total Pb in the sediments were mainly from parent material, industrial emission and vehicle exhaust with the mean contributions of 38.2%, 51.3% and 10.5%, respectively, calculated by a three-end-member model of Pb isotopic ratios. Highlights: Level of 16 heavy metals in intertidal surface sediments of Quanzhou Bay was studied. The sediments had been polluted by some heavy metals including Pb. Pb isotopic compositions in the sediments and the potential sources were determined. A three-end member model was applied to estimate the contributions of Pb sources. Industrial emission was the major anthropogenic Pb contributor in the sediments.